Health priority-setting for official development assistance in low-income and middle-income countries: a Best Fit Framework Synthesis study with primary data from Ethiopia, Nigeria and Tanzania - Xiaoxiao Jiang Kwete; Yemane Berhane; Mary Mwanyika-Sando; Ayo Oduola; Yuning Liu; Firehiwot Workneh; Smret Hagos; Japhet Killewo; Dominic Mosha; Angela Chukwu; Kabiru Salami; Bidemi Yusuf; et al. (BMC, 2021)
Abstract Background Decision making process for Official Development Assistance (ODA) for healthcare sector in low-income and middle-income countries involves multiple agencies, each with their unique power, priorities and funding mechanisms. This process at country level has not been well studied. Methods This paper developed and applied a new framework to analyze decision-making process for priority setting in Ethiopia, Nigeria, and Tanzania, and collected primary data to validate and refine the model. The framework was developed following a scoping review of published literature. Interviews were then conducted using a pre-determined interview guide developed by the research team. Transcripts were reviewed and coded based on the framework to identify what principles, players, processes, and products were considered during priority setting. Those elements were further used to identify where the potential capacity of local decision-makers could be harnessed. Results A framework was developed based on 40 articles selected from 6860 distinct search records. Twenty-one interviews were conducted in three case countries from 12 institutions. Transcripts or meeting notes were analyzed to identify common practices and specific challenges faced by each country. We found that multiple stakeholders working around one national plan was the preferred approach used for priority setting in the countries studied. Conclusions Priority setting process can be further strengthened through better use of analytical tools, such as the one described in our study, to enhance local ownership of priority setting for ODA and improve aid effectiveness.